ANALYSIS OF THE IMPACT OF DEVELOPING THE BUSINESS AND INVESTMENT ENVIRONMENT ON TOURISM SPENDING IN IRAQANALYTICAL STUDY OF OPPORTUNITIES AND CHALLENGES (World Bulletin of Management and Law, 2023)
Tourism activity is an important economic activity at the global and national levels, as the tourism industry plays an important role in promoting and strengthening the national economy at the macro level, as it is one of the main pillars of service economics. The development of the business and investment environment is crucial to promote economic growth and achieve sustainable development in any country, and in the context of the State of Iraq the tourism sector has tremendous potential for development and growth, which can contribute significantly to strengthening the economy, providing jobs and promoting social development. In order to exploit this great potential, it is necessary to develop the business environment and create the appropriate conditions to attract tourism investments. The study found that the tourism industry has a number of positive economic effects on tourism development models, which result in significant gains to contribute to the development process, Through the development of the business and investment environment for the private sector, which is the beating heart of the economies of countries and with the support of the public sector through various mechanisms, the most important of which is activating financing policies, stimulating legislation and preparing infrastructure plans for national tourism to make a difference in the tourism industry to contribute to supporting the national economy and one of the tributaries of its revenues through financial returns derived from tourism spending.